DREAM AND LOVE IN EDGAR ALLAN POE’S POEMS: A DREAM WITHIN A DREAM AND ANNABEL LEE - Nur Israfyan Sofian; Irianto Ibrahim (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
This paper studies Edgar Allan Poe's two poems; A Dream within a Dream and Annabel Lee, from a stylistic perspective. These two poems describe the desperation and hope to stay in love while they applied linguistic deviation as the medium to raise the aesthetical emotion. The aesthetical emotion within these two poems came after the linguistic level and style markers used within the poems. Therefore, this paper intended to uncover the meaning of those two poems from linguistic deviation and style markers used from the stylistic perspective. The data for this paper were collected from both poems and analysed with the qualitative description approach. This paper found that the linguistic deviation in these poems can express the aesthetic emotion the author intended to convey about the dream to love.